The impact of the new Saudi civil transactions system on the provisions of sponsorship (The International Journal for Scientific Research, 2026)
This research aims to study the impact of the new Saudi Civil Transactions Law, issued on 29/11/1444 AH (corresponding to 18/6/2023 CE), on the provisions of the guarantee contract. This is achieved through an analysis of the legal texts contained in Articles (578) to (606), and a comparison with established Islamic jurisprudence and Saudi judicial precedent prior to the issuance of the law.The research employs a descriptive-analytical approach to examine the legal texts and demonstrate their contribution to developing the legal position of the parties involved in the guarantee: the creditor, the debtor, and the guarantor. The research reached several conclusions, most notably: the law successfully transferred the provisions of the guarantee from the realm of jurisprudential and judicial interpretation to a written legal framework that achieves clarity and legal certainty; and it introduced new provisions that strengthened the protection of the guarantor, such as their discharge of liability if the creditor loses the guarantees (Article 588), their right to notify the creditor to take legal action against the debtor (Article 589), and the regulation of the right of recourse against the debtor (Article 597). The system also achieved a fair balance between the interests of the three parties and contributed to reducing discrepancies in judicial interpretations related to guarantee disputes.In light of the findings, the research recommended issuing interpretive guides for the application of guarantee provisions, intensifying training programs for legal professionals, raising legal awareness about the systemic implications of guarantees, developing standardized documentation models for guarantee contracts, and enhancing integration between the Civil Transactions Law and related regulations.
Keywords: Saudi Civil Transactions Law; Guarantee Contract; Personal Guarantee; Creditor; Debtor; Guarantor; Islamic Jurisprudence; Judicial Interpretation; Legal Certainty; Judicial Stability; Saudi Vision 2030